Ferulic Acid Alleviates Lipid and Bile Acid Metabolism Disorders by Targeting FASN and CYP7A1 in Iron Overload-Treated Mice - Yaxu Liang; Jun Qi; Dongming Yu; Zhibo Wang; Weite Li; Fei Long; Shuai Ning; Meng Yuan; Xiang Zhong (MDPI AG, 2024)
Iron overload is a common complication in various chronic liver diseases, including non-alcoholic fatty liver disease (NAFLD). Lipid and bile acid metabolism disorders are regarded as crucial hallmarks of NAFLD. However, effects of iron accumulation on lipid and bile acid metabolism are not well understood. Ferulic acid (FA) can chelate iron and regulate lipid and bile acid metabolism, but its potential to alleviate lipid and bile acid metabolism disorders caused by iron overload remains unclear. Here, in vitro experiments, iron overload induced oxidative stress, apoptosis, genomic instability, and lipid deposition in AML12 cells. FA reduced lipid and bile acid synthesis while increasing fatty acid β-oxidation and bile acid export, as indicated by increased mRNA expression of PPARα, Acox1, Adipoq, Bsep, and Shp, and decreased mRNA expression of Fasn, Acc, and Cyp7a1. In vivo experiments, FA mitigated liver injury in mice caused by iron overload, as indicated by reduced AST and ALT activities, and decreased iron levels in both serum and liver. RNA-seq results showed that differentially expressed genes were enriched in biological processes related to lipid metabolism, lipid biosynthesis, lipid storage, and transport. Furthermore, FA decreased cholesterol and bile acid contents, downregulated lipogenesis protein FASN, and bile acid synthesis protein CYP7A1. In conclusion, FA can protect the liver from lipid and bile acid metabolism disorders caused by iron overload by targeting FASN and CYP7A1. Consequently, FA, as a dietary supplement, can potentially prevent and treat chronic liver diseases related to iron overload by regulating lipid and bile acid metabolism.